Legal Standing of Pre-Contractual Good Faith Principle as a Law Reformation of Indonesian Contract Law - N. Ike Kusmiati (GoAcademica Research & Publishing, 2020)
Good faith plays an important role in a contract since it holds a dominant position either during pre-contractual phase or when a contract is executed. However, pre-contractual good faith in Indonesian Civil Code is not recognized as such there is no legal assurance. In fact in pre-contractual stage, the parties already put some investment based on trust and hope, however, they faced dead end and they did not reach an agreement. This was tinted with the fading of wall between two major legal systems: Common Law System and Civil Law System as a result of dynamic in business relation involving countries bringing some developments in contract law. The extension in the substance of good faith in Article 1338 verse (3) of the Civil Code should not be implemented so grammartically that good faith does not only appear during the execution of the contract but it should also be interpreted during the whole process of the contract that good faith should lay the foundation of the parties relation both in pre-contractual phase and during the contract such that the good faith in Article 1338 verse (3) of Civil Code functions dynamically. In UPICC, the provision of good faith is stipulated in Article 1, 7 stressing on the importance of good faith and fair dealing. This stressing underlays the process of contract agreement. Good faith should be interpreted and formulated during the whole process of contract. Under the traditional doctrine of Common law, court cannot punish the defendant because Common Law system does not recognize the good faith principle in negotiation process. Nevertheless, modern law contract waives the legal assurance to reach a substantial justice that good faith is not only applied in a contractual relation but also in a pre-contractual. Meaning, good faith does not only bind upon matters explicitly stated in the agreement, but also upon ones that traditionally are required by appropriateness, tradition, or the law as stipulated in Article 1339 of the Civil Code and Article 6:248 of Netherlands NBW. The good faith and fair dealing principles should be the underpinning of contract law. Each party should uphold the principles of good faith and fair dealing in the whole process of the contract starting from negotiation, contract arrangement, the execution of the contract as far as the termination of the contract particularly in the reformation of Indonesian future contract law